Игра в ящик: роман / Сергей Солоух - Солоух Сергей ("Самое время!", 2011)
Экземпляры: (20111215) / Инвентарный номер: 47394 / Цена: 206.26; 440.59; 260.03 / Сис.шифр: Р2 47394 / Авт.знак: С 60 / ББК: Р2